UPAYA PENINGKATAN SADAR PAJAK MELALUI PERGURUAN TINGGI OLEH KPP PRATAMA JOMBANG - Kholis Firmansyah; Rohmat Hidayat (JoEMS (Journal of Education and Management Studies), 2020)
This study aims to find out the efforts made by KPP Pratama Jombang to increase tax awareness of the taxpayer. One of them is in collaboration with universities to socialize the importance of tax awareness. The method used in this research is a descriptive-qualitative method. The steps used in data collection are observation, interview and documentation. The steps of data analysis are: editing, classifying, analyzing and concluding. The results showed that the efforts to increase tax awareness made by KPP Pratama Jombang were conducting socialization to leaders, lecturers and students at universities in Jombang, collaborating with universities, accepting internship students at KPP Pratama, incorporating tax awareness materials in General Obligatory Curriculum such as Indonesian, Citizenship Education, Pancasila Education and Religious Education (Islam, Christianity, Catholicism, Hinduism, Buddhism, Konghuchu)